Estudos metanalíticos de indicadores produtivos em suinocultura - Lanferdini, Eloiza (2015)
The objective in this study was (1) to evaluate the effect of piglets‟ birth weight on performance and carcass characteristics and (2) to evaluate the nutrient intake in pregnant sows, by means a meta-analytic study. Two databases were built based on systematic review techniques. The database 1 was composed of 28 articles (published from 2000 to 2014) and used to evaluate the birth weight effect. The database 2 was composed for 12 articles having primiparous sows and 24 articles with multiparous sows (published from 2004 to 2014) to assess the nutrition of pregnant sows. Lighter piglets at birth showed (P<0.05) lower organs weights. The piglet birth weight influenced (P<0.05) average weight and weight gain in all subsequent growth phases, with heaviest piglets at birth showing weight 6.61 kg higher at slaughter (150 days of age) in relation to lightest piglets at birth. The feed efficiency in growing-finishing phase improved (P<0.05) in heaviest piglets at birth. The age at slaughter to achieve 110 kg of body weight decreased (P<0.05) in 12.1 days in piglets born heavier compared with animals born lighter. Piglets with different birth weights did not differ (P>0.05) in relation to the carcass characteristics and meat quality. However, lightest piglets at birth showed higher relative belly weight (0.5%; P<0.05), lower weight ham (4.4%; P<0.05) and lower weight of the heart and liver at slaughter (6.8%; P<0.05) compared to piglets with highest birth weight. The studies with sows (database 2) mainly evaluated the nutrition in late pregnancy, using predominantly the same amount of feed provided during the pregnancy. Most of the studies showed nutrient intake higher than the recommended by the latest versions of the National Research Council - NRC (2012) and the Brazilian Tables (2011). The piglets‟ birth weight interferes in organ weights at birth and performance in later growth stages. Studies published in the last 14 years using higher nutrient levels that the recommendations of nutritional requirements for pregnant sows and providing the same amount of feed.